Successful Treatment of a Massive Metoprolol Overdose Using Intravenous Lipid Emulsion and Hyperinsulinemia/Euglycemia Therapy. Issue 5 (22nd April 2015) - Barton, Cassie A.; Johnson, Nathan B.; Mah, Nathan D.; Beauchamp, Gillian; Hendrickson, Robert
<x xml:space="preserve">Abstract</x> Adrenergic β‐antagonists, commonly known as β‐blockers, are prescribed for many indications including hypertension, heart failure, arrhythmias, and migraines. Metoprolol is a moderately lipophilic β‐blocker that in overdose causes direct myocardial depression leading to bradycardia, hypotension, and the potential for cardiovascular collapse. We describe the case of a 59‐year‐old man who intentionally ingested ~7.5 g of metoprolol tartrate. Initial treatment of bradycardia and hypotension included glucagon, atropine, dopamine, and norepinephrine. Despite these treatment modalities, the patient developed cardiac arrest. Intravenous lipid emulsion (ILE) and hyperinsulinemia/euglycemia (HIE) therapies were initiated during advanced cardiac life support and were immediately followed by return of spontaneous circulation. Further treatment included gastric lavage, activated charcoal, continued vasopressor therapy, and a repeat bolus of ILE. The patient was weaned off vasoactive infusions and was extubated within 24 hours. HIE therapy was continued for 36 hours after metoprolol ingestion. A urine β‐blocker panel using mass spectrometry revealed a metoprolol concentration of 120 ng/ml and the absence of other β‐blocking agents. To date, no clear treatment guidelines are available for β‐blocker overdose, and the response to toxic concentrations is highly variable. In this case of a life‐threatening single‐agent metoprolol overdose, the patient was successfully treated with HIE and ILE therapy. Due to the increasing frequency with which ILE and HIE are being used for the treatment of β‐blocker overdose, clinicians should be aware of their dosing strategies and indications.